APPLICATION OF ZEOLITE FOR IMPROVEMENT OF GROWTH MEDIA AND GROWTH OF OIL PALM SEEDLING - Winarna Winarna; E. S. Sutarta (Jurnal Zeolit Indonesia, 2005)
Zeolite has been known for improvement of soil fertility through increasing the cation exchange capacity. The objective of this research is to evaluate the application of zeolite for improvement of growth media and growth of oil palm seedling. The research has been conducted in the oil palm seedling research area of Aek Pancur using completely randomized design. The soils used for media are Typic Paleudults, Typic Udipsamments, and Typic Hapludults. The treatment composed of 4 zeolite dossages 0,50, 100, and 150 g/polybag. The results showed that application of zeolite to soils improved the properties of soils, especially cation exchange capacity. Application of zeolite as soil amelioration in the seedling of oil palm did not significantly improve the growth and absorption of nutrients during 11 months. In general, application of zeolite with the dosage of 100 g/polybag improve the growth and absorbtion of nutrients compared to without zeolite application. On the othe hand, application of 150 g zeolite/polybag decrease the growth and absorbtion of nutrients.